Moisture absorption and dimensional stability of poplar wood impregnated with sucrose and sodium chloride - Petr, Pařil; Aleš, Dejmal (Maderas. Ciencia y Tecnología, 2025)
This paper deals with the effect of vacuum-pressure impregnation of Poplar wood (Populus alba) by aqueous solutions of sucrose and sodium chloride on its physical properties. Groups of samples with different concentrations of substances in the aqueous solution were compared within each other and also with a reference (non-impregnated) group. The specimens from all groups were tested for density, moisture absorption and dimensional stability. The obtained data were statistically analysed and compared each other. The most satisfying final properties were achieved in impregnation of sucrose with concentration of 6,25 g/100 ml H2O. The retention was 31 kg m-3 (WPG around 8 %). The values of ASE (anti-swelling efficiency) reached to 36 % and MEE (moisture exclusion efficiency) was reduced by 33 %.